Transition Pathways in Cylinder-Gyroid Interface (Communications in Computational Physics, 2022)
When two distinct ordered phases contact, the interface may exhibit richand fascinating structures. Focusing on the Cylinder-Gyroid interface system, transition pathways connecting various interface morphologies are studied armed with theLandau–Brazovskii model. Specifically, minimum energy paths are obtained by computing transition states with the saddle dynamics. We present four primary transitionpathways connecting different local minima, representing four different mechanismsof the formation of the Cylinder-Gyroid interface. The connection of Cylinder and Gyroid can be either direct or indirect via Fddd with three different orientations. Underdifferent displacements, each of the four pathways may have the lowest energy.